The problem and promise of coproduction - Geoffrey Goodwin (London School of Economics and Political Science (LSE), Department of International Development, 2018)
Interest in 'coproduction' has continued to grow since Elinor Ostrom introduced the concept to the development scholarship two decades ago. The idea that multiple actors often interact to coproduce public goods and services helped shift development thinking away from one-size-fits-all policy prescriptions based on free market principles to a more nuanced position that recognises organizational and institutional diversity. However, while Ostrom's approach to coproduction provides a useful starting point to think about how states and societies interact to produce public goods and services, it fails to capture important dimensions of the process. The diverse scholarship that has extended and critiqued her work has provided a fuller picture. Yet, important gaps remain. The aim of this paper is to fill some of these holes and push the boundaries of coproduction analysis. Drawing on the case of water coproduction in Ecuador, it highlights three issues that are overlooked or undeveloped in the existing literature: a) the history and ubiquity of coproduction b) the form of state-society relations that emerge through the process and c) the relationship between coproduction, commodification and accumulation. Through the discussion of these three issues and a critical review of the existing scholarship, the paper will seek to lay the foundation for a critical approach to coproduction analysis.
Keywords: 330; coproduction; state-society relations; autonomy; water; Ecuador